Active-site solvent replenishment observed during human carbonic anhydrase II catalysis. (2018) - Kim, Jin Kyun; Lomelino, Carrie L.; Avvaru, Balendu Sankara; Mahon, Brian P.; McKenna, Robert; Parkc, SangYoun; Kim, Chae Un
No abstract available